2019
DOI: 10.1007/s00248-019-01417-4
|View full text |Cite
|
Sign up to set email alerts
|

What Goes Up Might Come Down: the Spectacular Spread of an Endosymbiont Is Followed by Its Decline a Decade Later

Abstract: Facultative, intracellular bacterial symbionts of arthropods are usually vertically transmitted with great fidelity, and may dramatically affect host biology and reproduction. The length of these symbiont-host associations may be thousands of years, and while symbiont loss is predicted, there have been very few observations of a decline of symbiont infection from high frequencies to low. In a population of the sweetpotato whitefly species (Bemisia tabaci MEAM1) in Arizona, USA, we documented the frequency decl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 77 publications
0
32
1
Order By: Relevance
“…Therefore, some unknown factors in the field must be responsible for the decline in Rickettsia infection. There are evidences that the decline might be driven by changes in context-dependent fitness effects of hosting the bacteria [31]. In contrast to other studies, the dynamics of Rickettsia in this study were observed in a shorter period of time and could have been driven by specific environmental factors.…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…Therefore, some unknown factors in the field must be responsible for the decline in Rickettsia infection. There are evidences that the decline might be driven by changes in context-dependent fitness effects of hosting the bacteria [31]. In contrast to other studies, the dynamics of Rickettsia in this study were observed in a shorter period of time and could have been driven by specific environmental factors.…”
Section: Discussioncontrasting
confidence: 96%
“…However, the same study reported the increasing of infection of Hamiltonella, Rickettsia and Wolbachia in MED species individuals from 2015 to 2017 [32]. In laboratory conditions, Rickettsia is vertically transmitted by female whiteflies at high rates ranging from 98%-99% [31,33]. Therefore, some unknown factors in the field must be responsible for the decline in Rickettsia infection.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Rickettsia bellii spread to near fixation in an Arizona population of the sweet potato whitefly (Bemisia tabaci) in 2011, but then declined in frequency (p = 0.36) in 2017 (Bockoven et al 2019). Our 2018 sampling on São Tomé revealed that wYak frequencies vary between low and high altitudes, and wSan varied temporally from 2015 to 2018.…”
Section: Discussionmentioning
confidence: 74%
“…Some studies have investigated the functions of these symbionts on the biology of the whitefly hosts. For example, a Bellii group Rickettsia was found to confer fitness benefits and promote female bias for its MEAM1 whitefly host in the USA in the 2000s (Himler et al ., 2011); however, later the mutualism of this Rickettsia with its whitefly host was found to be conditional and the frequency of the Rickettsia in wild populations of its whitefly host declined rapidly from near‐fixation in 2011 to 36% in 2017 (Cass et al ., 2016; Hunter et al ., 2017; Bockoven et al ., 2020). Intriguingly, the same Rickettsia infections of MEAM1 whitefly in Israel was reported to confer no advantage (Chiel et al ., 2009) and was more recently undetected in the field (Brumin et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%